From Access to Documents to Consumption of Information: The European Commission Transparency Policy for the TTIP Negotiations - Coremans, Evelyn (2017)
To increase transparency of the Transatlantic Trade and Investment Partnership (TTIP) negotiations, the European Commission has reformed existing information sharing systems for trade policy. The Commission has moved from a strategy of providing transparency in the form of access to documents to one of access to information, geared specifically towards enhancing consumption of the available information. In both public and institutional transparency policy, the width of the target audience and the depth of the information have increased, and the manner of provision has shifted from reactive to proactive provision of information. As a result, the TTIP is now being coined as the most transparent trade negotiation ever in the EU’s history and a pilot project for transparency policy in future trade negotiations. The article adopts a supply-centred perspective to explain a transparency policy that goes beyond the legal minimum imposed by formal requirements. It relies on interview data of the changes brought about in inter-institutional relations since 2014, basic quantitative and qualitative analysis of document material, and a five-month participatory observation by the author in the secretariat of the European Parliament’s Committee on International Trade.